(untitled) (Research, Society and Development, 2024)
Castleman’s disease is an uncommon medical condition characterized by abnormal growth of lymphatic cells. Also called giant nodular hyperplasia or lymphoid angiofollicular hyperplasia, it can result in increased lymphoid tissue and tumor formation. The present study aims to report the case of a patient diagnosed with Castleman’s disease after an incidental finding on an imaging exam and describe its manifestations, radiological findings, and approaches. Methodology: data collection will take place in the patient’s medical records at a hospital in Patos de Minas, during July and November 2023, after obtaining parental consent and patient assent. Information such as sex, age, date of diagnosis, symptoms, and imaging exam results will be recorded and presented descriptively through a case report. In addition, a search will be carried out in the Google Academy, Scielo, Pubmed, BVS, and LILACS databases to gather relevant national and international articles to enrich the research.